Bioconcentration of Chromium (Cr) on The Soft Tissue of Mussels (Perna viridis, Linnaeus 1758) in Tambak Lorok Waters, Semarang - Siti Rudiyanti; Suryanti Suryanti; Churun Ain (Universitas Diponegoro, 2023)
Industrial development provides economic benefits, but also increases the concentration of waste pollution which affects the aquatic environment of Tambak Lorok on the North Coast of Central Java. The existence of this waste will affect the life of the biota in it, such as mussels (Perna viridis). The heavy metal Chromium is the focus of research, considering that its presence in large quantities which accumulates in the human body causes health problems. The aims of the research were to determine the content of heavy metal Cr in the waters, sediments, and soft tissue of mussels, to determine the bioconcentration of heavy metal Cr in mussels, and to determine the tolerable intake of weekly consumption of the mussels cultivated in Tambak Lorok waters. The content of Cr in water samples, sediment, and mussel soft tissue was measured the APHA 3111B-2012 method, US EPA SW-846/3050 B-1996 SM 3111B-2012 method, and SSA method. The calculation of bioconcentration mussels, using the bioconcentration factor and Maximum Tolerable Intake. The heavy metal content of Cr in the water column was 0.015 – 0.025 mg.L-1 (upper the quality standard), in sediment was 25.12 – 28.72 mg.kg-1(lower the quality standard), and in the soft tissue of mussels was 0.155 – 0.265 mg/kg (upper the quality standard). The bioconcentration factor of metal Cr in mussels is classified as low, which is around 10.35 – 14. The maximum tolerable intake for mussels was 6,078 kg/week, it is considered safe for consumption.